Optimalisasi Manajemen Kasus untuk Perlindungan Perempuan dan Anak di Kabupaten Bima - Irmansah Irmansah; Israfil Israfil (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study aims to analyze the difficulties faced by Social Sciences (IPS) teachers in the learning process of Sociology subjects in class XI of SMA Negeri 2 Langgudu. The focus of this study is to identify factors that inhibit the effectiveness of learning, both from the internal aspects of teachers and external school environments and students. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through in-depth interviews, direct observation, and documentation. The research informants consisted of six IPS teachers selected using purposive sampling techniques, namely teachers who actively teach Sociology subjects. The data analysis procedure uses the Miles and Huberman interactive model, including the stages of data reduction, data presentation, and drawing conclusions. The results of the analysis show that the main difficulties faced by IPS teachers include limited mastery of information technology, the absence of school policies that require the use of IT-based media, and the diversity of student characteristics that affect the achievement of learning objectives. In addition, teachers experience obstacles in adapting the Merdeka Curriculum and time constraints in implementing project-based learning (P5). These findings indicate that improving teacher competency, school policy support, and curriculum implementation assistance are important aspects in overcoming obstacles to Sociology learning in schools.